Digestive Megaformaciones chagasic myocarditis and in the Hospital Obrero de Lima - Cornejo Donayre, Alberto (1965)
The first Peruvian cases of myocarditis and digestive megaformaciones in patients with Chagas' disease is presented. The diagnosis was established by the reaction of complement fixation test and xenodiagnosis. The authors conducted extensive clinical study and highlight the cardiac and gastrointestinal findings. One was advanced chronic myocarditis that led to the sudden death, facilitating necropsy. The second patient represents the first case of me-Peruvian gacolon Chagas. Commenting on these cases highlights the importance and significance of the presence of Chagas disease among workers insured Peru; the epiderniológico meaning and impact on work capacity. Emphasis on the danger of spread transfusion sets.